First check list of vacular flora from Reserva Provincial Parque Luro, La Pampa (Argentina) (Semiárida, 2024)
The Parque Luro Provincial Reserve is, thus far, the only conservation site of the Caldén Forest in the province of La Pampa. Although it was declared a protected area in the 1990s, it does not yet have a complete floristic checklist. In this work, the first complete and systematically the floristic list of the area is documented. The catalogue was obtained from the SRFA Herbarium database and through comprehensive floristic censuses, carried out between 2020 and 2022. The study accounted for a total of 225 taxa. Of the 51 botanical families present in the area, the most represented are Poaceae, Asteraceae and Solanaceae. Those taxa identified as South American native represent the 81 % of the total recorded flora, and the 31 % of the total are corresponding to endemic species to Argentina. These values justify the continuation of studies to account for the role of the protected area as a biodiversity reserve. The presence of exotic species could be linked to the proximity to fields with agricultural-growing uses, as well as the use within the site as a tourist area and fire barrier. The dominant life forms were terophytes, camephytes and hemicryptophyts, which is expected for a semi-arid environment. The abundance of natives, justify the incorporation of protected areas and the safeguarding of them, as in this case, the conservation of the Caldenal.
Keywords: native flora; natural reserves; SRFA herbarium; protected areas; caldenal